Farmers' Motivation in Farming Horticultural Crops (Case Study: Indigenous Papuan Farmers in Aipiri Village, East Manokwari District) - William Jeremmy Kaunang; Amestina Matualage; Obadja A. Fenetiruma (International Journal of Educational and Life Sciences, 2024)
This research was conducted in Aipiri Village, East Manokwari District, with the aim of examining the motivations of indigenous farmers (OAP) in horticultural farming in Aipiri Village, East Manokwari District. The research employed survey and case study methods. The sampling method used in this research was simple random sampling. The population of this study consisted of indigenous farmers (OAP) engaged in horticultural farming in Aipiri Village, East Manokwari District. The results of this study indicate that farmers have a high motivation for existence needs, with 70.6% of farmers motivated to meet their children's educational expenses and 72.5% motivated to fulfill supporting educational needs for their children. For relatedness needs, 60.8% of farmers were motivated to gain new experiences from other farmers, and 70.6% were motivated to provide experiences to other farmers. For growth needs, 62.7% of farmers were motivated to use modern equipment, and 82.4% were motivated to implement the internet.